Bank Risk, Capitalisation and Technical Efficiency in the Vietnamese Banking System - Tu DQ Le (Australasian Accounting, Business and Finance Journal, 2018)
This study investigates the interrelationships among bank efficiency, capital, and risk in Vietnamese banking between 2007 and 2011 by using the three-stage least squares in a simultaneous equations framework. The efficiency scores of individual banks are obtained from the Data Envelopment Analysis with the use of financial ratios. The average efficiency level of Vietnamese banks is relatively low, suggesting that there is a room for Vietnamese banks to further improve their efficiency so as to achieve world best practice. The findings also show a negative relationship between bank risk and capital, suggesting that credit risk and financial leverage are reinforcing each other. Furthermore, our findings also indicate that an improvement in bank efficiency precedes an increase in risk. In addition, the results suggest that more efficient and lower risk banks are associated with higher capital levels. Finally, the findings show that more-diversified banks tend to be higher risk-taking and have greater performance. Therefore, our findings have important implications for bank prudential supervision and underline the importance of increasing the minimum charter capital requirement in the future to support financial stability objectives.
Keywords: Bank efficiency; capital ratios; bank risk; DEA-financial ratios; diversification; 3SLS